Marketing Strategy Homestay in Kebangsaan Tourism Village Wonorejo - Fondina Gusriza; Garsione Agni Andrea; A. Muammar Alawi (Nusantara Science and Technology Proceedings, 2022)
Kebangsaan Tourism Village is one of the buffer villages located next to the Baluran National Park. This tourist village has enormous tourism potential to be developed. The development of tourism is also accompanied by the number of homestays growing which began to develop from 2017 and currently there are 9 homestays listed. The purpose of this study was to analyze the Marketing Strategy Homestay in Kebangsaan Tourism Village Wonorejo. This research is descriptive with a qualitative approach. Data obtained by conducting interviews, observations and literature study. Data analyzed using the 7P marketing theory. The results of the study indicate that the marketing strategy has not been maximized yet.